HCV Integrated Care: A Randomized Trial to Increase Treatment Initiation and SVR with Direct Acting Antivirals - Erik J. Groessl; Lin Liu; Marisa Sklar; Samuel B. Ho (International Journal of Hepatology)
Background and Aims. Psychiatric or substance use disorders are barriers to successful HCV antiviral treatment. In a randomized, controlled trial (RCT), the effects of HCV Integrated Care (IC) for increasing treatment rates and sustained viral response (SVR) were studied with direct acting antivirals (DAA). Methods. In 2012-13, VA patients, whose screening was positive for depression, PTSD, or substance use (N=79), were randomized to IC or Usual Care (UC). IC consisted of brief psychological interventions and case management. The primary endpoint was SVR among patients followed for an average of 16.6 months. Results. 42% of the study participants were previously homeless and 79% had HCV genotype 1. Twice as many IC participants (45%) initiated treatment compared with UC participants (23%) (χ2 = 4.59, p=0.032). Among those treated, SVR rates did not significantly differ (IC: 12/18 = 67%; UC: 5/9 = 55%; p=0.23). Among all randomized participants, IC participants trended toward better SVR rates (30.0% versus 12.8% in UC; p=0.07). Conclusions. Although first-generation DAAs are no longer used, this smaller RCT helps confirm the results of a larger multisite RCT showing that Integrated Care results in higher treatment initiation and SVR rates among HCV-infected persons with comorbid psychological disorders. Integrated mental health services can facilitate treatment among the most challenging HCV patients, many of whom have not been successfully treated. This trial is registered with ClinicalTrials.gov number NCT00722423.